2004
DOI: 10.1007/s00417-004-0957-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct stimulation of optic nerve by electrodes implanted in optic disc of rabbit eyes

Abstract: The visual cortex can be activated by direct microelectrical stimulation of the optic nerve. The acute implantation of the wire microelectrodes into the optic disc by a transvitreal approach is feasible and results in only limited damage to the optic nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
3
27
1
Order By: Relevance
“…These results suggest that optic nerve stimulation with penetrating electrodes can have much lower thresholds than that with surface electrodes. Compared with our data, the lower threshold of stimulating the optic nerve head reported by Fang et al [9] was probably due to the difference in the material and the exposed surface of stimulating electrodes. In their study, platinum wire was used as stimulating electrode, and the exposed surface of stimulating electrode was about 0.4× 10 −4 cm 2 larger than ours.…”
Section: Histologycontrasting
confidence: 60%
See 2 more Smart Citations
“…These results suggest that optic nerve stimulation with penetrating electrodes can have much lower thresholds than that with surface electrodes. Compared with our data, the lower threshold of stimulating the optic nerve head reported by Fang et al [9] was probably due to the difference in the material and the exposed surface of stimulating electrodes. In their study, platinum wire was used as stimulating electrode, and the exposed surface of stimulating electrode was about 0.4× 10 −4 cm 2 larger than ours.…”
Section: Histologycontrasting
confidence: 60%
“…Histological analysis of transverse sections of the optic nerve of the eyes implanted with electrodes showed that the stimulating electrode was penetrated into the optic nerve, and the depth of the implantation was about 0.5 mm. Their results demonstrated that cortical responses could be elicited by this approach [8,9,38]. However, the optimal stimulus parameters to activate the optic nerve have not been investigated systematically.…”
Section: Histologymentioning
confidence: 94%
See 1 more Smart Citation
“…ON visual prosthesis has been considered a potential approach to restore vision for the blind with retinal degeneration diseases [32][33][34][35][36][37][38][39][40][41]. Our group proposed a visual prosthesis based on intraorbital ON stimulation with penetrating electrodes, which has been demonstrated to evoke visual cortical responses with lower current thresholds and improved spatial resolution compared with surface cuff electrode ON stimulation [36,37,41].…”
Section: Discussionmentioning
confidence: 99%
“…Visual prostheses have proved to be a promising way to restore partial functional vision for patients with RP. Three major types of visual prostheses have been investigated according to the stimulation locations: cortical prostheses [3][4][5][6][7], retinal prostheses using epi-and subretinal stimulation , and optic nerve (ON) prostheses [31][32][33][34][35][36][37][38][39][40][41]. The retinal prosthesis is the most developed type among the three, and the Argus II epiretinal prosthesis has been approved by the European CE and the US FDA for clinical use [23].…”
Section: Introductionmentioning
confidence: 99%